Сакральні пам’ятки західних областей УРСР в умовах антирелігійної кампанії 1958–1964 років - Мочкін, Сергій Анатолійович; Mochkin, Sergiy А. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті на численних прикладах висвітлено непросту долю нерухомих та рухомих об’єктів сакральної (культової) спадщини західних областей радянської України під час здійснення в 1958–1964 роках на території республіки антирелігійної кампанії. Наведено окремі факти порятунку культових пам’яток історії й культури парафіянами, небайдужими до святинь шанувальниками старовини. A difficult fate of sacred (religious) movable and immovable monuments of western regions of Ukraine during the Soviet antireligious campaign 1958–1964 period was covered on the basis of archival documents and published materials. The attention is focused on the actions of the Communist Party and the Soviet government. They were aimed at closing the religious buildings. Many of them are unique architectural monuments, the destruction of sacred utensils situated therein. It was noted that as a result of a large-scale offensive against the religion and the church in order to eliminate the so-called «spiritual opium» and secure a monopoly position communist world sacred cultural heritage of the region has suffered irreparable losses. There are individual facts of salvation of the religious monuments, sacred utensils by indifferent to the shrines of antiquity fans, parishioners.
The Sacred Monuments of Western Regions of URSR in Circumstances of Antireligious Companies from 1958 to 1964.
Keywords: anti-religious campaign; sacred (religious) monuments; church; Roman Catholic church; monastery; religious association; антирелігійна кампанія; сакральні (культові) пам’ятки; церква; костел; монастир; релігійна громада